Animal Metropolis Histories of Human-Animal Relations in Urban Canada - Sethna, Christabelle; Dean, Joanna; Ingram, Darcy (Canadian History and Environment, 2017)
Animal Metropolis brings a Canadian perspective to the growing field of animal history, ranging across species and cities, from the beavers who engineered Stanley Park to the carthorses who shaped the city of Montreal. Some essays consider animals as spectacle: orca captivity in Vancouver, polar bear tourism in Churchill, Manitoba, fish on display in the Dominion Fisheries Museum, and the racialized memory of Jumbo the elephant in St. Thomas, Ontario. Others examine the bodily intimacies of shared urban spaces: the regulation of rabid dogs in Banff, the maternal politics of pure milk in Hamilton and the circulation of tetanus bacilli from horse to human in Toronto. Another considers the marginalization of women in Canada's animal welfare movement. The authors collectively push forward from a historiography that features nonhuman animals as objects within human-centered inquiries to a historiography that considers the eclectic contacts, exchanges, and cohabitation of human and nonhuman animals. With contributions by: Kristoffer Archibald, Jason Colby, George Colpitts, Joanna Dean, Carla Hustak, Darcy Ingram, Sean Kheraj, William Knight, Sherry Olson, Rachel Poliquin, and Christabelle Sethna